Computer and Information Science 2015 - Lee, Roger (Studies in Computational Intelligence,, 2016)
This edited book presents scientific results of the 14th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2015) which was held on June 28 - July 1, 2015 in Las Vegas, USA. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. Research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them.